Single Parent Responsibilities and Efforts to Children Education: Analysis of Physical, Intellectual and Spiritual - Saiin, Asrizal; Valijon Ghafurjonovich Macsudov; Aliem Amsalu (Multicultural Islamic Education Review, 2024)
Researchers observed that mothers have a large role and responsibility, and single mothers need to be taken seriously in various ways. Therefore, this research aims to answer how child care should be carried out by a single parent, in this case, the mother, considering that a mother's role is very important in educating children. The research method used is qualitative research which produces descriptive data, namely by using a review of documents (books, journals, research results) that are relevant to the research. Following the data obtained and also based on the nature of this research, namely descriptive, the author uses qualitative methods, namely non-statistical. Data analysis is carried out in the following steps: data reduction, data display, and drawing conclusions or verification. The research results state that the concept of a single parent refers to an individual who carries out the role of caring for children in a family structure without the involvement of a husband or life partner. Mothers as single parents can instill three forms of basic education in their children, namely physical, intellectual and spiritual education. The role of single parents as those responsible for children's education today can introduce the importance of maintaining health (physical), directing children on the right path to achieving success in life (intellectual), and educating and understanding children about religion and beliefs (spiritual).